The problem with pilots how physicians, engineers, and airpower enthusiasts redefined flight - Schultz, Timothy Paul 1966- (Johns Hopkins University Press, 2018)
"Pilots were a major problem in aviation development. They were exposed as feeble, vulnerable, and inefficient as aircraft flew higher, faster, and farther. Pilots asphyxiated or got the bends at high altitudes; they blacked out during high-G maneuvers; they spun into the ground after encountering clouds or fog; and they found innumerable ways to commit fatal errors. This is the story of how physicians and engineers, spurred by airpower enthusiasts seeking to advance the military potential of aviation, sought new means to address these problems and bridge the widening gap between human and machine performance. It provides an original view of how their efforts connected the technological, the medical, and the human element and effected changes that transformed the pilot's role and redefined flight. Schultz explores the major changes in the pilot-aircraft relationship that transpired primarily between World War One and the end of World War Two and applies them to modern flight. Archival resources illuminate the pilot's evolution, and theories of technological change inform the innovations and institutional imperatives that elevated the roles of life scientists and engineers"--Provided by publisher